Herbal Products: Benefits, Limits, and Applications in Chronic Liver Disease. (6th September 2012) - Del Prete, Anna; Scalera, Antonella; Iadevaia, Maddalena Diana; Miranda, Agnese; Zulli, Claudio; Gaeta, Laura; Tuccillo, Concetta; Federico, Alessandro; Loguercio, Carmelina
Abstract : Complementary and alternative medicine soughts and encompasses a wide range of approaches; its use begun in ancient China at the time of Xia dynasty and in India during the Vedic period, but thanks to its long-lasting curative effect, easy availability, natural way of healing, and poor side-effects it is gaining importance throughout the world in clinical practice. We conducted a review describing the effects and the limits of using herbal products in chronic liver disease, focusing our attention on those most known, such as quercetin or curcumin. We tried to describe their pharmacokinetics, biological properties, and their beneficial effects (as antioxidant role) in metabolic, alcoholic, and viral hepatitis (considering that oxidative stress is the common pathway of chronic liver diseases of different etiology). The main limit of applicability of CAM comes from the lacking of randomized, placebo-controlled clinical trials giving a real proof of efficacy of those products, so that anecdotal success and personal experience are frequently the driving force for acceptance of CAM in the population.